A morphological and geometrical study of historical minarets in the North of Algeria - Beldjilali, Said; Benkari, Naima; Namourah, Zahir; Varum, Humberto (Budownictwo i Architektura / Civil and Architectural Engineering, 2024)
The Islamic heritage constitutes a very precious treasure in Algeria, especially the places of worship (mosques), which reflect the symbol of this heritage. They are considered important landmarks in cities through architectural elements such as the dome and the minaret. Minarets are used by the muezzin to invite people to pray; they were previously built near the mosque or inside it, next to the prayer room. Later, they appeared as angular towers of mausoleums. This research is part of an analytical study of the minarets in Algeria during the medieval period (Bani Hamad, Moravid, Zayyanid, Marinid, and Ottoman) which were selected and then classified according to their various typologies (dimensions, forms, designs, etc.), and evolution over time. The main objectives of this work are to search for the forms that determine the typology of the minarets of each period. It also examines the correlation between dimensions and geometric parameters employed in the design conception of these minarets. The research followed a monographic method that relies on field observation and documentation, while including a thorough reading of history. The results show that the constant form of the vertical section of the minaret, with the same dimensions between the top and bottom, represents two-thirds of the main tower of the minarets. We also conclude that the square shape of the horizontal section of the minaret represents two-thirds of the main tower of the minarets, which expresses the most earthquake-resistant form. These dimensions play a pivotal role in enhancing the minaret's visual allure and architectural equilibrium, in addition to their earthquake resistance virtues.